Benefits of l-theanine supplementation and its possible role in clinical use - review - Karol Womperski; Justyna Woźniak; Julia Szymonik; Sebastian Szopa; Jagoda Elias (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Green tea has been a meaningful element of various cultures among the world for ages and its benefits for human health are widely known. Discovery of its ingredients facilitated the profound research of their positive role and mechanisms of action. One of them - l-theanine - seems to have a multidirectional influence on human health. Methods and materials: A review of chosen literature from PubMed database, GoogleScholar database between the years 2000-2023 was conducted using the following keywords: "theanine", "theanine cognition", "theanine brain activity", "theanine neural activity", "theanine neuroprotection", "theanine stress", "theanine cancer", "theanine immunity", "theanine safety", "theanine caffeine", "theanine metabolism" Aim of study: Review of current knowledge on l-theanine, its benefits for health, mechanisms of action, possible applications in clinical use and safety. Results:  L-theanine has a profitable influence on cognitive performance, stress management, neuroprotection, immunity and exhibits anti-cancer properties while having virtually no detrimental side effects. Conclusions: Further research on application of l-theanine in clinical use is necessary as studies carried out on humans included only a limited number of participants.